Solve for x:
3x + y = 9 is the same as -3x + 9 = y
Since you now know the equation for y you can plug it into the first equation:
3x + (-3x + 9) = 9
After solving, you will see that x cancels out and that 9 = 9.
Solve for y:
3x + y = 9 is the same as 3 - y/3 = x
Since you now know the equation for x you can plug it into the first equation:
3(3 - y/3) + y = 9
After solving, you will also see that y cancels out and that 9 = 9.
The Answer:
There are actually two posibble answers:
1.) y = 9 and x = 0
If you plug the numbers in then you will get 3(0) + (9) = 9
The answer is 9 = 9
2.) y = 0 and x = 3
If you plug the numbers in then you will get 3(3) + (0) = 9
This will also give you the answer 9 = 9
Chat with our AI personalities
y=-2/3x
Their graphs are.
3x-y = 9 2x+y = 6 Add both equations together: 5x = 15 x = 3 and y = 0
5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3
y = 3x + 1